2006
DOI: 10.1111/j.1469-0691.2006.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an immune diagnostic assay based on RD1 selected epitopes for active tuberculosis in a clinical setting: a pilot study

Abstract: A previous case-control study reported that an in-vitro interferon (IFN)-gamma response to early secreted antigenic target (ESAT)-6 selected peptides was associated with active tuberculosis (A-TB). The objective of the present pilot study was to evaluate the diagnostic accuracy of this assay for TB disease in a clinical setting. An IFN-gamma ELISPOT assay was performed on samples from patients with suspected A-TB using two peptides selected from ESAT-6 protein and three peptides selected from culture filtrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 22 publications
3
59
1
2
Order By: Relevance
“…Preliminary doubt that these assays can be applied to HIV-infected people has been raised (16,17) although ELISpot-based analyses report encouraging sensitivity (73-90%) for active HIV-associated tuberculosis in both children and adults (18,19). There have been relatively few published three-way comparisons of these tests (20)(21)(22), and no study has systematically assessed the decrement in sensitivity that might be conferred by HIV infection in comparable HIVinfected and uninfected persons. Further, studies in developing country environments are few.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Preliminary doubt that these assays can be applied to HIV-infected people has been raised (16,17) although ELISpot-based analyses report encouraging sensitivity (73-90%) for active HIV-associated tuberculosis in both children and adults (18,19). There have been relatively few published three-way comparisons of these tests (20)(21)(22), and no study has systematically assessed the decrement in sensitivity that might be conferred by HIV infection in comparable HIVinfected and uninfected persons. Further, studies in developing country environments are few.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…There is evidence that commercial IGRAs are highly sensitive for detecting LTBI [2], and have a high specificity that is unaffected by bacille Calmette-Guérin (BCG) vaccination. Although IGRAs were designed as assays for LTBI, these tests do not discriminate between active disease and LTBI [5,6]. Moreover, IGRAs do not distinguish between a recently acquired infection and remote LTBI [7].…”
mentioning
confidence: 99%
“…First, LEE et al [2] demonstrated that T-SPOT.TB has higher sensitivity than QuantiFERON-TB Gold in the diagnosis of culture-confirmed active TB disease, and this finding has also been reported by GOLETTI et al [3]. Whilst active TB disease is clearly not the same as LTBI, it might be hypothesised that this difference in sensitivity is also true in LTBI.…”
mentioning
confidence: 77%